Dos encontros entre as infâncias, a educação e a cidade: o que revelam as pesquisas - Simões, Juliana Brum (2022)
This article aims to investigate the relationships that are built between childhood, city and education in the light of study carried out in Brazilian Universities between the years 2014 and 2021. It is inspired by the experience of Movimento BrincaCidade - started in Rio de Janeiro, in 2015, - and is guided by the conception of education that occurs in both non-formal and informal environments - in territories, places, meetings and relationships – considering that being in the city with children gives the opportunity for the coexistence between people of different generations. The study starts from a bibliographical review (BOTELHO, CUNHA and MACEDO, 2011), comprising the search, selection and analysis of the works, reaching fifteen studies, among dissertations and theses, which are analyzed in order to understand how the relationships between childhoods, education and the city have been addressed, as well as which themes are linked or stand out from it. The studies were focused in the Bank of Dissertations and Theses of the Coordination for the Improvement of Higher Education Personnel, CAPES, in the field of Education studies. As theoretical support, we consider the studies of Sarmento (2005, 2007, 2011, 2018) about children in their different childhoods, as producers of culture and their relations with the urban space and Lopes (2006, 2008, 2021), on children as authors who are also built in their relations with the environment, perceiving the city in their own way. Araújo’s studies (2017, 2018, 2021) supports the conception of education as public coresponsibility and the importance of thinking about an epistemology of the city in the company of children.